Annexins: A family of calcium binding proteins with variety of roles in plant development and abiotic stress tolerance - Faizan, Mohammad; Ashoka, Hadagali; Karabulut, Fadime; Alam, Pravej; Ahmed, S. Maqbool; Khan, Ira; Ahmad, Naved (Elsevier, 2024)
Plant annexins are a multigene family of phospholipid-binding, calcium-dependent proteins that respond to signals and environmental challenges as plants grow and develop. Plant annexins are functionally unique due to their ATPase/GTPase, peroxidase, and calcium (Ca2+) channel-regulating activities. They play a major role in controlling many different aspects of cellular and metabolic functions, plant growth and development, and reactions to both biotic and abiotic environmental stimuli. In this review, we provide an overview of how intracellular and extracellular annexins work, mechanism of reactive oxygen species (ROS) and annexins, highlight recent developments of the roles of annexins in abiotic stress tolerance in plants, and emphasize the role of annexins in plant growth and development.
Keywords: Extracellular annexins; Stress; G -protein; Signal mechanism